2020
DOI: 10.22175/mmb.9470
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic Proteome Profile and Internal Color of Beef Longissimus Lumborum Steaks Cooked to Different Endpoint Temperatures

Abstract: The complex relationship between endpoint temperature, sarcoplasmic proteome, and internal color in cooked steaks is yet to be examined. The objective of the present study was to characterize the changes in sarcoplasmic proteome and their influence on the internal color of beef longissimus lumborum (LL) steaks cooked to different endpoint temperatures. Two 2.5-cm-thick LL steaks were fabricated from 9 beef strip loins and were cooked to an internal endpoint temperature of either 60°C (C-60) or 71°C (C-71). Coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Salim et al . (2020), examined relationship between endpoint temperature and sarcoplasmic proteome of steaks. They reported that high internal endpoint temperature reduced the number of sarcoplasmic protein spots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salim et al . (2020), examined relationship between endpoint temperature and sarcoplasmic proteome of steaks. They reported that high internal endpoint temperature reduced the number of sarcoplasmic protein spots.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that direct/indirect heat application and application time parameters affect this difference observed in the sarcoplasmic protein profile of the samples. Salim et al (2020), examined relationship between endpoint temperature and sarcoplasmic proteome of steaks. They reported that high internal endpoint temperature reduced the number of sarcoplasmic protein spots.…”
Section: Sds-page Profile Of Sarcoplasmic and Myofibrillar Proteinsmentioning
confidence: 99%
“…The sarcoplasmic proteins found in beef muscles have been investigated using gel-based proteomic analyses focusing on two-dimensional (2D) gel electrophoresis with label-free approach (Joseph et al, 2012;Suman et al, 2014;Canto et al, 2015;Nair et al, 2018;Yu et al, 2018;Salim et al, 2020). In meat science studies, tandem mass tag (TMT) proteomics is a very recent gel-free approach that has been used for exploring postmortem biochemical and cellular processes in bovine (Zhai et al, 2020), ovine (Li et al, 2018), and porcine (Liu et al, 2018) muscles.…”
Section: Introductionmentioning
confidence: 99%